2019
DOI: 10.1021/acs.jced.8b00844
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Correlation of Liquid–Liquid Equilibria Data for Ternary System Isopropyl Acetate + Isopropanol + Water at Different Temperatures

Abstract: The liquid−liquid equilibrium (LLE) data for the (isopropyl acetate + isopropanol + water) ternary system were determined experimentally using an equilibrium cell from 298.15 to 323.15 K at 101.3 kPa to obtain the fundamental data guiding the separation process of isopropyl acetate and isopropanol mixtures. The solvents' extraction capacity was assessed by the solute distribution coefficient and selectivity. Othmer−Tobias and Bachman correlations for tie lines were used to assess the smoothed trend of the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
1
18
1
Order By: Relevance
“…Table lists D and S values, and the comparison with the literature , is shown in Figures and . It can be seen from Table that the S gradually decreases with the addition of IPA, and the system of 1-octanol decreases more obviously than that of n -propyl acetate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table lists D and S values, and the comparison with the literature , is shown in Figures and . It can be seen from Table that the S gradually decreases with the addition of IPA, and the system of 1-octanol decreases more obviously than that of n -propyl acetate.…”
Section: Resultsmentioning
confidence: 99%
“…The D value of 1-octanol is greater than that of n -propyl acetate. This work was compared with the extraction capacity of isopropyl acetate researched by Zhang and cyclohexanone researched by Wang, and it was found that the order of D value from large to small is 1-octanol, cyclohexanone, n -propyl acetate, and isopropyl acetate. The results show that when 1-octanol, cyclohexanone, and n -propyl acetate are used as extractants, the extraction rate is higher, meaning fewer extractants are needed to achieve the same extraction goal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermometer was calibrated with zero-scale and multiple-point. The experimental instruments and sampling method introduced in this work were identical to those reported in the previous publications. , The chromatographic peak area fraction was converted to the mole fraction by determining the relative mole correction factor for each substance using the internal standard method, and finally, all the components in the conjugation phase were quantified. Among them, isopropanol with a mass fraction purity of >99.90% (GC) was used as the standard compound.…”
Section: Methodsmentioning
confidence: 99%
“…However, azeotropic distillation and extractive distillation require more energy consumption and complicated equipment. Nowadays, liquid-liquid extraction (Demakhin et al 2011;Zhang et al 2019;Cumplido et al 2020) is used in the separation of azeotropic mixtures due to its energy-savings.…”
Section: Introductionmentioning
confidence: 99%